Sample storage and fasting times affect blood serum and plasma components in fasted and non-fasted broiler chickens - Clauber Polese; Lucas Wachholz; Cinthia Eyng; Leandro Dalcin Castilha; Jansller Luiz Genova; Rayanne Andrade Nunes; Nilton Rohloff, Jr.; Paulo Cesar Pozza; Lidiane Ines Datsch; Arele Arlindo Calderano; José Geraldo de Vargas, Jr.; Vaneila Daniele Lenhardt Savaris; et al. (Journal of Applied Poultry Research)
Summary: We determined the impacts of blood fraction, fasting and samples storage times on the total protein, albumin, globulin, uric acid, creatinine concentrations, and alkaline phosphatase activity in 70 45-d-old male Cobb 500® broiler chickens. Blood was collected at 2-h intervals (0, 2, 4, 6, 8, 10, and 12 h). Serum and plasma fractions were stored at -20°C and analyzed on 0, 30, and 60 days. Serum and plasma uric acid concentrations increased with increasing storage time, while a reduction in creatinine concentration and serum alkaline phosphatase activity was observed. Serum creatinine and alkaline phosphatase showed a quadratic effect, with a peak concentration of 0.208 mg dL-1 at 4 h and 32 min of fasting, and the lowest concentration of 2933 U l-1 at 8 h of fasting, respectively. Plasma total protein, albumin, and creatinine showed a quadratic effect, with a peak concentration of 35.46 g l-1 at 7 h and 48 min, 15.36 g l-1 at 10 h and 48 min, and 0.18 mg dL-1 at 7 h and 46 min, respectively. Overall, serum and plasma can be used for the analysis of total protein, albumin and globulin, with a fasting time of 12 h and storage for up to 60 days at -20°C. Both serum and plasma fractions can be used for uric acid analysis, but immediate analysis after sample collection is recommended, and a 12-h fast can be used. It is recommended to use serum for creatinine and alkaline phosphatase analysis, with storage for up to 30 days at -20°C.